(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
Soils present a biodiversity of bacteria, part of this microflora is cultivable, it can be estimated, characterized and identified. Four zones each comprising three sites were sampled in Brazzaville in the Republic of Congo. Phenotypic characterization, molecular identification and proteolytic capacity of soil bacteria were conducted. One of the factors, the pH was measured, the pH values were between 6 and 7. From the classical microbiology techniques, we counted the total flora of the microorganisms in (CFU / g.103), it is between 47 Â± 11.2 and 214 Â± 58.2 and that of bacteria of the genus Bacillus from 51.3 Â± 5.0 to 74 Â± 30.7. Cocci and bacilli were obtained, Gram- and Gram + bacteria distinguished, all bacteria were catalase +, some had sporulation, others not. Thirty-one (31) isolates were phenotypically characterized and 16S rDNA PCR was performed. Ten (10) strains were sequenced and the phylogenetic classification of the identified strains presented. Blastn’s research on the 16S rDNA sequences of the different strains shows similarity rates (96.77% -100%) and E. value (9.00E-93 -0.0), these two indices allowed the identification of the strains studied. The percentages of the identified strains are as follows: Bacillus cereus (20%) = MN6 and MN14, Bacillus pumilus (10%) = MN7, Bacillus thuringiensis (10%) = MN12, B sp. (10%) = MN17, Bacillus subtilis (10%) = MN26, Staphylococcus haemolyticus (10%) = MN8, Staphylococcus saprophyticus (10%) = MN21, Staphylococcus sp. (10%) = MN22, Staphylococcus gallinarum (10%) = MN24. The phylogenetic tree shows that the bacteria belong to two main monophyletic genera, the genus Bacillus and the genus Staphylococcus. The proteolytic capacity of Bacillus bacteria was assessed in parallel with growth. The optical density was between (0.8- 0.93) and proteolytic enzyme production between (9-20mm). The parallelism between growth and enzymatic production shows that the two phenomena are distinct.